Compressor maintenance supported by tribodiagnostics - Ales, Zdenek; Pexa, Martin; Peterka, Bohuslav; Holek, Martin (Manufacturing Technology Journal, 2010)
Quality product is dependent on reliable and serviceable manufacturing facility, which is influenced by effective and timely performed maintenance, including checking and refilling of lubricants and other vital fluids. For assessing the state of lubricants and parts of manufacturing machinery, it is possible to use a series of analysis including, for example particle counter and particle shape classifier LaserNet Fines-C, flash point, kinematic viscosity, water content, determination of solid particles, wear metals, etc. Each analysis used to assess technical condition of lubricating oil and machine and helps to carry out maintenance at appropriate intervals, which are directly affected by the technical condition. Such maintenance system achieves economic savings over the maintenance performed in a tightly planed and schedule. The paper compares examples of oil analyses of two compressors.
Keywords: wear; maintenance; tribodiagnostics; LaserNet Fines-C